The Making of a Monster: Alienation, Dehumanisation, and Consumerism in American Psycho and I Am Legend - Matyáš, Jan (Univerzita Pardubice, 2025)
This master's thesis explores horror literature as a vehicle for cultural and social critique in the post-World War II era. It focuses on the novels I Am Legend (1954) by Richard Matheson and American Psycho (1991) by Bret Easton Ellis. Through thematic analysis and close reading, the thesis examines how both texts reflect contemporary anxieties related to alienation, consumerism, dehumanisation, and the erosion of moral and mental structures. Furthermore, this thesis employs key theoretical frameworks, including Julia Kristeva's theory of abjection, Sigmund Freud's concept of the uncanny, existentialist theories by Jean-Paul Sartre and Albert Camus, and Jean Baudrillard's postmodern critique. It also outlines the cultural and historical background of each novel, namely the Cold War era and the neoliberal 1980s. The analytical section focuses on three central themes and presents a comparative perspective on how the figure of the monster, the protagonist, and human identity evolve across different moments in modern history.
Keywords: hororová fikce; kritika společnosti; odcizení; dehumanizace; desenzitizace; eroze morálky a psychického zdraví; konzumerismus; existencialismus; abjekce; Americké Psycho; Já, legenda; horror fiction; social criticism; alienation; dehumanisation; desensitisation; erosion of morality and sanity; consumerism; existentialism; abjection; American Psycho; I am legend